2018
DOI: 10.14414/jebav.v20i2.878
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Fiscal Decentralization, Institutional Transformation, and Regional Revenue on Income Disparities between Provinces in Indonesia

Abstract: This study aims to determine the impacts of fiscal decentralization, institutional transformation, and regional revenue to the income disparity among the provinces in Indonesia. This study uses panel data with the number of runs 528 pieces of data that includes 33 provinces in Indonesia period 2000-2015. The data were taken from the Central Bureau of Statistics (BPS) and Bank Indonesia. They were analyzed using a multiple linear regression analysis. The results show that tax revenue sharing fund and natural re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…A similar research finding also articulated that fiscal decentralization did not impact income inequality (Cevik & Correa-Caro, 2020;Fan et al, 2020). Likewise, Mudayen & Maridjo (2017) also found an inverse relationship between special allocation funds and income inequality between provinces in Indonesia. The special allocation fund for assignment supports accelerating the development of basic service infrastructure focused on priority locations (sub-districts) in the district/city.…”
Section: Etikonomisupporting
confidence: 54%
“…A similar research finding also articulated that fiscal decentralization did not impact income inequality (Cevik & Correa-Caro, 2020;Fan et al, 2020). Likewise, Mudayen & Maridjo (2017) also found an inverse relationship between special allocation funds and income inequality between provinces in Indonesia. The special allocation fund for assignment supports accelerating the development of basic service infrastructure focused on priority locations (sub-districts) in the district/city.…”
Section: Etikonomisupporting
confidence: 54%
“…Dalam pelaksanaan desentralisasi fiskal itu sendiri, dikenal adanya filosofi money follow function sebagai prinsip utama yang harus diperhatikan dan dilaksanakan (Fatoni, 2020;Haryanto, 2018;Mudayen and Maridjo, 2018;Siregar and Badrudin, 2017). Prinsip tersebut mengandung makna bahwa segala bentuk penyerahan kewenangan Pemerintah Pusat kepada Pemerintah Daerah, seyogianya disertai dengan penyerahan sumber-sumber pendanaannya (Bahl, 2000;Korompot and Warongan, 2017).…”
Section: Pendahuluanunclassified
“…This in turn catalyzes growth. The literature reveals that tax revenue, amidst many sources of government funds, constitutes the main source of government revenue globally (see Mudayen and Maridjo, 2018; Ama and Omodero, 2017; Sule, 2016; Nwosu and Okafor, 2014). Conversely, various studies have also identified oil proceeds, grants, national savings, aid, and debts as essential sources of government revenue (Okwori and Sule, 2016; Onyele and Nwokoacha, 2016).…”
Section: Introductionmentioning
confidence: 99%